Physicochemical Properties of Conjugated Linoleic Acid‐Rich Soy Oil. (22nd September 2013) - Ruan, Chuan Min; Proctor, Andrew
Abstract: CLA‐rich soy oil (CLARSO) has been produced by linoleic acid isomerization in soy oil TAG. The objective was to determine the physicochemical properties of the novel CLARSO relative to conventional refined bleached deodorized soy oil (RBDSO). Iodine value decreased in CLARSO samples despite unsaturation being unchanged, probably because conjugated double bonds in triacylglycerol (TAG) of CLARSO impede the complete addition of iodine. Thermal analysis by differential scanning calorimetry showed the melting point temperature increased with the increase in the CLARSO CLA concentration, and melting point broadening occurred in CLA contained samples. Dynamic viscosity of CLARSO conducted from 4 to 44 °C increased with the increase in CLA concentration, relative to RBDSO. Greatest viscosity differences occurred at the lower temperatures. Refractive indices and density were not greatly affected. The change in physical properties was attributed to the increased intermolecular hydrophobic interaction force due to conjugated double bonds and trans, trans isomers, relative to RBDSO. This may provide hard fat characteristics that may be useful for use in producing margarine or shortenings. Furthermore, the higher viscosity at refrigerator temperatures may be useful in salad oil and refrigerated sauces to enable suspension of particles and maintain a rich, thicker texture.